Pengembangan area wisata ATV dan hammock di Dusun Trucuk, Kalurahan Triwidadi - Binarti, Floriberta; Setiadi, Amos; Antarangga, Eppatta Kaelasa; Yuansha Putra, Patric Chrisna (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2023)
The development of the ATV and hammock tourism area is part of the design of the community-based tourism region along the Progo River in Trucuk Hamlet. The design theme is natural and based on ecological principles. Minimal environmental intervention with a maximum provision of tourist facilities is carried out by by conserving the local vegetation maximally and selecting environmentally friendly construction materials and permeable surface materials. The ATV tourist area is the end of a series of areas with a bridge connecting this tourist area with the Progo River bank area on the other side. This area provides an ATV point and track and a playground. The hammock tourist area in the middle of the region functions as a resting point where visitors can lie down in the hammock, eat at a floating restaurant, and take a boat down the Progo River.